Rift migration and transition during multiphase rifting: Insights from the proximal domain, northern South China Sea rifted margin. (January 2021) - Hao, Shihao; Mei, Lianfu; Shi, Hesheng; Paton, Douglas; Mortimer, Estelle; Du, Jiayuan; Deng, Peng; Xu, Xinmin
Abstract: Multiphase rifting with tectonic quiescence intervals is one of the most distinguishing features during the evolution of rift basins and rifted margins, which always produce oceanward rift migration. However, this law seems to be challenged in the proximal domain of the northern South China Sea (SCS) rifted margin. Based on high-quality 2D/3D seismic reflection data and borehole data from the Zhu 1 Depression located in the northern SCS, we examine the temporal and spatial variations of rifting. The regional unconformity, cyclicity of faulting, and rotation in extension direction indicate that the Zhu 1 Depression experienced continuous two-phase rifting with four stages but without distinct tectonic quiescence intervals. In Stage 1 of Syn-rift 1, rifts were distributed across the whole depression. They began to migrate towards the continent in stage 2 of Syn-rift 1, which continued until stage 1 of Syn-rift 2, and then migrated to the east. Rifting was also accompanied by a clockwise rotation of the strikes of fault systems, which were ~N065°E and ~N080°E in stage 1 and stage 2 of Syn-rift 1, respectively, and then rotated to ~ S085°E during Syn-rift 2. We suggest that the interactions between the pre-existing basement fabrics and the regional stress fields rotating clockwise can account for this rotation and the eastward rift migration. The rift migration towards the continent is supposed to be caused by the emplacement of the high-velocity lower crust (HVLC) underneath the Dongsha Uplift, which may initiate in the Eocene. The distinctive multidirectional, multiphase, and multi-mechanical rift migration reflects the uniqueness of the SCS rifted margin. This study helps us understand the complicated rifting process that interacts with pre-existing fabrics, regional stress field, and the emplacement of high-velocity lower crust. Highlights: Rift migration towards the continent rather than the ocean. The clockwise rotation of the strikes of fault systems during multiphase rifting. Pre-existing faults, stress fields, and crustal strength affect rift migration. The emplacement of HVLC in the northern SCS may initiate in the Eocene. The proximal unusual tectono-magmatism responds to the uniqueness of the SCS margin.